2021
DOI: 10.21608/ejhm.2021.207095
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Triangular Fibro-cartilaginous Complex Injuries of The Wrist Using High Resolution Ultrasound versus Magnetic Resonance Imaging

Abstract: Background: Triangular fibrocartilage complex (TFCC) may be assessed using ultrasound (US) because of its wide availability, mobility, low cost, and lack of radiation. When it comes to TFCC imaging, MRI is the gold standard, although US can provide a more detailed picture of the disease. Objective: Comparing and contrasting the use of ultrasound (US) and magnetic resonance imaging (MRI) in the detection of triangular fibrocartilaginous complex injuries of the wrist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…TFCC injury or degeneration was discovered by MRI in 16 joints but only by US in 14 joints, hence there was a high degree of agreement between the two methods in the present investigation. Our results are supported by Kadry et al [13] who reported that wrist discomfort or reduced wrist mobility was reported by 35 individuals with a mean age of 39 ± 13.18 years old. The US detected 18 positive cases with TFCC injury with a percentage of 51.4%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…TFCC injury or degeneration was discovered by MRI in 16 joints but only by US in 14 joints, hence there was a high degree of agreement between the two methods in the present investigation. Our results are supported by Kadry et al [13] who reported that wrist discomfort or reduced wrist mobility was reported by 35 individuals with a mean age of 39 ± 13.18 years old. The US detected 18 positive cases with TFCC injury with a percentage of 51.4%.…”
Section: Discussionsupporting
confidence: 91%
“…In both the Physical Medicine and Radiology Departments at Cairo University Hospitals, highfrequency linear probes of Samsung MEDISON UGEOH60 (5)(6)(7)(8)(9)(10)(11)(12)(13) were used for US tests; in 5 cases, GE Logic pro6 (7)(8)(9)(10)(11) was used instead.…”
Section: Ultrasonographic Examinationmentioning
confidence: 99%